DETERMINATION NON-SPESIFIK STANDARIZATION OF FOREST ONION BULBS EXTRACT (ELEUTHERINE AMERICANA MERR) - Yusril Mokodompit (PHARMACON, 2023)
This research aims to find out result from the test non-specific standardization extract forest onion (Eleutherine americana Merr). Extract forest onion (Eleutherine americana Merr.) obtained by maceration method, the extract obtained was observed by parameter non-specific which include drying shrink, water content, total dust content, and acid insoluble dust. Parameter non-specific compared with reference determation standart parameter. The result testing this parameter non-specific extract dayak onion from passi village obtain shrink drying 0,1137 %, water content 0,1545 %, total dust content 0,3931 %, and dust acid insoluble 9,8062 %. According the result of extract dayak onion standart shrink drying parameter, water content, and total dust content, meanwhile for acid insoluble dust parameter it is not accordance with because procces washing that is not clean so there a lot impurity